2007
DOI: 10.1038/sj.ijo.0803773
|View full text |Cite
|
Sign up to set email alerts
|

Promoter adiponectin polymorphisms and waist/hip ratio variation in a prospective French adults study

Abstract: Background: Adiponectin expression and plasma concentrations are decreased in human and animal models of obesity. Several single nucleotide polymorphisms (SNPs) in the adiponectin gene are known to influence the plasmatic concentration of the encoded protein. Some of these adiponectin polymorphisms have been associated with BMI in cross-sectional studies. Objective: The aim of our study was to examine the longitudinal relationships between adiponectin gene polymorphisms and anthropometric indices. Design: Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 29 publications
0
17
1
3
Order By: Relevance
“…The + 276G allele was associated with higher BMI in Italians (116) but with lower BMI in Swedish and African Americans (120,121) . Higher waist : hip ratio was found in carriers of the -11391A allele (122) and there are reports of increased risk of insulin resistance and type 2 diabetes associated with the -11391 G/G genotype (105,109) .…”
Section: Adipoq Gene Polymorphismsmentioning
confidence: 99%
“…The + 276G allele was associated with higher BMI in Italians (116) but with lower BMI in Swedish and African Americans (120,121) . Higher waist : hip ratio was found in carriers of the -11391A allele (122) and there are reports of increased risk of insulin resistance and type 2 diabetes associated with the -11391 G/G genotype (105,109) .…”
Section: Adipoq Gene Polymorphismsmentioning
confidence: 99%
“…6,17 Currently, a limited number of cohort studies evaluated associations between genetic variation in candidate genes and waist. [18][19][20] In the last decade, it became feasible and affordable to analyze a large number of single nucleotide polymorphisms (SNPs) simultaneously. Genome-wide association studies, a hypothesis-free approach to find genetic areas associated with a trait, identified associations between genetic variations in the INSIG2, FTO, CTNNBL1 and MC4R gene and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…If there was a genotype -11391A and 11377C, WHR was significantly higher compared to other haplotypes. Also AC/AC-haplotype carriers had higher levels of adiponectin than the carriers of GG/GG-haplotype (p < 0.0001) [47].…”
Section: Discussionmentioning
confidence: 97%